Egg Freezing in Islamic Law: A Study on Its Relevance to the Concept of the Maṣlaḥah Family in Muslim Society - Shafiqoh, Hazikahtus; Firdawaty, Linda; Susilo, Edi (Universitas Islam Negeri Alauddin Makassar, 2025)
The advancement of reproductive technologies offers new opportunities for women in planning pregnancy, one of which is egg freezing. Originally developed for medical purposes—particularly for women undergoing chemotherapy—egg freezing has since been adopted for non-medical reasons such as career planning or the absence of a suitable partner. This shift has sparked ethical, legal, and religious debates, especially within Muslim communities that adhere to sharī‘ah-based principles. This study aims to explore the permissibility and implications of egg freezing in Islamic law and to assess its compatibility with the concept of the maṣlaḥah family. Employing a qualitative methodology with a library research approach, this research draws on primary sources (Qur’an, ḥadīth, classical fiqh, and contemporary fatwas), as well as secondary and tertiary literature. The analysis is framed through the lens of maqāṣid al-sharī‘ah and the ethical foundations of the maṣlaḥah family. The findings indicate that egg freezing may be deemed permissible under Islamic law if specific conditions are met—particularly that fertilization occurs within a lawful marriage and safeguards are in place to prevent lineage confusion. When aligned with Islamic values, egg freezing can contribute to responsible reproductive planning and psychological preparedness, enhancing the realization of a maṣlaḥah family. However, concerns remain regarding commercialization, socio-economic inequality, and technological dependency. These challenges highlight the need for robust regulatory frameworks and value-based education to guide ethical application.